Análisis para el control de seguridad y acceso vehicular en la ciudadela privada “Mirador del Norte” en la ciudad de Guayaquil. - Peralta Méndez, Madelyn Arianna (2024)
The privately owned citadel “Mirador del Norte” in the city of Guayaquil faces significant security challenges due to its strategic location and high-value assets. Ensuring the security of residents, visitors, and assets is crucial to maintaining the citadel’s reputation and attractiveness. This project aims to conduct a comprehensive analysis for security and vehicle access control in the citadel, focusing on identifying vulnerabilities, assessing risks, and proposing effective measures to mitigate them. The study will employ a mixed-methods approach, combining both qualitative and quantitative data collection and analysis techniques. A review of existing security technologies will be conducted, complemented by surveys, interviews, and observations of security personnel, residents, and visitors. The analysis will identify potential security threats, including unauthorized access, theft, vandalism, and terrorist activities, and assess the citadel’s current security posture. The expected outcomes of this project include a significant reduction in security, improved response times, and increased safety for residents and visitors. The findings and recommendations of the study will provide valuable information for policy makers, security managers, and stakeholders in the citadel, allowing them to make informed decisions about security investments and strategies. Ultimately, this project will contribute to the development of a safer environment in the private citadel "Mirador del Norte" and serve as a model for other private communities in the city of Guayaquil.